2010
DOI: 10.3899/jrheum.090442
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Retreatment in Patients with Rheumatoid Arthritis with Previous Inadequate Response to Tumor Necrosis Factor Inhibitors: Results from the SUNRISE Trial

Abstract: Two courses of rituximab about 6 months apart resulted in improved and sustained efficacy at 1 year, compared with 1 course, with a similar safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
89
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 11 publications
8
89
0
3
Order By: Relevance
“…These results from the SUNDIAL II study indicate that the overall safety profile of RTX 2 × 500 mg when used in combination with a single biologic DMARD over 48 weeks is consistent with that reported previously in studies of RTX plus MTX or other nonbiologic DMARD 10,14,16 and in a study of RTX plus biologic DMARD 15 . The safety profile was consistent at 24 and 48 weeks, with the majority of patients receiving a second course of RTX during the study.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…These results from the SUNDIAL II study indicate that the overall safety profile of RTX 2 × 500 mg when used in combination with a single biologic DMARD over 48 weeks is consistent with that reported previously in studies of RTX plus MTX or other nonbiologic DMARD 10,14,16 and in a study of RTX plus biologic DMARD 15 . The safety profile was consistent at 24 and 48 weeks, with the majority of patients receiving a second course of RTX during the study.…”
Section: Discussionsupporting
confidence: 78%
“…In the current study, the 24-week rates of SAE (24.3 events/100 patient-yrs) and SIE (3.8 events/100 patient-yrs) were similar to those seen following 24 weeks of RTX treatment in the REFLEX study (21.6 and 5.2 events/100 patient-yrs, respectively), which involved patients refractory to TNF inhibitors and with similarly long disease duration (about 12 yrs) 10 . Similarly, the incidence of SAE (6.1%) and SIE (0.7%) in the retreatment population in the current study was consistent with those reported in the SUNRISE study (7% and 2%, respectively), in which patients received 2 courses of RTX 14 . It should be noted that patients in REFLEX and SUNRISE received the approved RTX dose of 2 × 1000 mg, in contrast to the lower 2 × 500 mg dose used in the current study, which is not an approved dosing regimen.…”
Section: Rheumatologysupporting
confidence: 81%
See 1 more Smart Citation
“…At baseline, most patients had moderate or high disease activity and comorbidities not typically observed in RCT, including a history of liver disease, peptic ulcer disease, and cancer 4,7,10 . The demographics and RA clinical characteristics of patients treated with RTX in our study were largely similar to US observational cohorts of patients with RA switching to their second or third anti-TNF 24 , with the exception of worse patient global, patient pain, and physician global assessments.…”
Section: Discussionmentioning
confidence: 99%
“…While RTX has been shown to be effective in randomized controlled trials (RCT) among patients with RA who have shown an inadequate response to anti-TNF 7,8,9,10 , these study populations may not accurately reflect real-world patients receiving RTX because of the strict inclusion and exclusion criteria of these trials 11,12 . In clinical practice, many patients initiating RTX have lower disease activity levels compared with those enrolled in anti-TNF RCT, a factor that further influences evaluations of effectiveness 12,13,14 .…”
Section: Rheumatologymentioning
confidence: 99%